Some approximation properties of new (p, q)-analogue of Balazs-Szabados operators - Hamal, Hayatem; Sabancigil, Pembe (Springer, 2021)
In this paper, a new (p,q)-analogue of the Balazs-Szabados operators is defined. Moments up to the fourth order are calculated, and second order and fourth order central moments are estimated. Local approximation properties of the operators are examined and a Voronovskaja type theorem is given.
Keywords: (p, q)-calculus; Moments; Bernstein operators; Balazs-Szabados operators; (p, q)-Balazs-Szabados operators